Further understanding of the mechanisms of electrochromic devices with variable infrared emissivity based on polyaniline conducting polymers. Issue 32 (26th July 2019) - Zhang, Leipeng; Wang, Bo; Li, Xiaobai; Xu, Gaoping; Dou, Shuliang; Zhang, Xiang; Chen, Xi; Zhao, Jiupeng; Zhang, Ke; Li, Yao
Abstract : Adaptive infrared (IR) electrochromic devices driven by electrical energy have considerable potential use in intelligent IR thermal management application in the future. Abstract : Adaptive infrared (IR) electrochromic devices driven by electrical energy have considerable potential use in intelligent IR thermal management application in the future. Polyaniline (PANI) is regarded as an ideal material for IR electrochromic devices due to its intrinsic IR electrochromic properties. However, despite extensive study focusing on improving the IR electrochromic properties of PANI, few experiments have been performed for in-depth study of the IR electrochromic mechanism of PANI or to improve its variable IR emissivity efficiency. Herein, an HClO4 -doped PANI porous film with excellent IR regulation ability was fabricated via in situ electrochemical deposition on an Au/microporous substrate, and the IR electrochromic mechanism of the PANI film was further elucidated. A combination of Raman spectra, UV-vis spectra, XPS analyses, transmittance curves and emittance curves of the PANI porous film in distinct conjugation states and corresponding dedoping states confirms that the most direct and critical factors for realizing the emissivity modulation of PANI films are the formation and the elimination of polarons and bipolarons delocalized on PANI chains. The key factor to achieve large amplitude emissivity modulation of PANI films is fully and effectively regulating the transformations between the various states of PANI. In addition, an IR electrochromic device was fabricated through assembly with HClO4 -doped PANI porous films. The device can realize modulation of the emittance variation from 0.735 to 0.316 (Δ ε = 0.419) and of the radiation energy variation from 273.503 to 117.661 W m −2 (Δ P = 155.842 W m −2 ) in the wavelength range of 2.5 to 25 μm. Furthermore, the device assembled with nanoporous PE possesses lower α ( s ) and excellent IR control capability. Also, this study shows that the device can change its color by electrical control in a thermal imaging system; these demonstrations suggest its potential for the future development of intelligent IR thermal management applications.